2007
DOI: 10.1104/pp.107.104794
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Regulation by DELLA Proteins of Trichome Development in Arabidopsis

Abstract: Gibberellins (GA) are known to influence phase change in Arabidopsis (Arabidopsis thaliana) as well as the development of trichomes, which are faithful epidermal markers of shoot maturation. They modulate these developmental programs in part by antagonizing DELLA repressors of growth, GIBBERELLIC ACID INSENSITIVE (GAI) and REPRESSOR OF ga1-3 (RGA). In this study, we have probed the relative roles played by RGA, GAI, and two homologs, RGA-LIKE1 (RGL1) and RGL2, in these processes and investigated molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 45 publications
2
41
1
Order By: Relevance
“…GA is required for trichome formation (Chien and Sussex, 1996;Perazza et al, 1998;Gan et al, 2007). Consistent with this, we also noticed that the GA biosynthetic mutant ga1-3 exhibited a nearly trichome-less phenotype (Figures 1A and 1B) and that the penta mutant (ga1-3 gai-t6 rga-t2 rgl1-1 rgl2-1, wild-type for RGL3) rescued the trichome-less phenotype ( Figures 1A and 1B).…”
Section: Ga Promotes Trichome Initiation In a Wd-repeat/bhlh/myb Compsupporting
confidence: 82%
See 1 more Smart Citation
“…GA is required for trichome formation (Chien and Sussex, 1996;Perazza et al, 1998;Gan et al, 2007). Consistent with this, we also noticed that the GA biosynthetic mutant ga1-3 exhibited a nearly trichome-less phenotype (Figures 1A and 1B) and that the penta mutant (ga1-3 gai-t6 rga-t2 rgl1-1 rgl2-1, wild-type for RGL3) rescued the trichome-less phenotype ( Figures 1A and 1B).…”
Section: Ga Promotes Trichome Initiation In a Wd-repeat/bhlh/myb Compsupporting
confidence: 82%
“…The hormonal signals gibberellin (GA) and jasmonate (JA) regulate many aspects of plant growth, development, and defense. GA plays essential roles in promotion of plant growth and development (Ueguchi-Tanaka et al, 2007;Harberd et al, 2009;Sun, 2011;Hauvermale et al, 2012;Davière and Achard, 2013), including root growth (Fu and Harberd, 2003;Ubeda-Tomás et al, 2008), seed germination (Kahn et al, 1957;Piskurewicz et al, 2008), hypocotyl elongation (Silk and Jones, 1975), leaf expansion (Achard et al, 2009), stem elongation (Kato, 1956), flower development (Cheng et al, 2004), trichome initiation (Chien and Sussex, 1996;Gan et al, 2006;Gan et al, 2007), and in repression of plant defense (Navarro et al, 2008). The GA receptors GA-INSENSITIVE DWARF1a/b/c perceive GA signals (Griffiths et al, 2006;Murase et al, 2008) and recruit DELLA proteins, including RGA (Silverstone et al, 1997), GAI (Peng et al, 1997), RGL1 (Wen and Chang, 2002), RGL2 (Lee et al, 2002), and RGL3 (Wild et al, 2012), for ubiquitination and subsequent degradation (Willige et al, 2007;Ariizumi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the dose response of petal number to GA, the production of sepal trichomes was strongly inhibited by 10 mM GA 3 application in both long days and neutral days (Fig. 8B), similar to Arabidopsis (Gan et al, 2007). Therefore, our results suggest that petal number variation in C. hirsuta responds to GA during photoperiodic flowering.…”
Section: Petal Number Regulation By Endogenous Signalscontrasting
confidence: 51%
“…In addition to the albino phenotype, we also found trichome initiation and stomata closure defects as a result of DXR disruption. It was previously reported that GAs play important roles in trichome development by regulating trichome-associated genes including GL1, GL3, and SPY [41][42][43][44][45]. As GAs are a class of important products derived from MEP-related isoprenoid biosynthetic pathways, it is reasonable to link DXR disruption to the observed trichome developmental defects.…”
Section: Discussionmentioning
confidence: 99%
“…The above data indi- cate that the MEP pathway and downstream metabolic pathways are coordinately regulated through the regulation of the expression levels of key enzymes involved. Trichome defects in dxr might result from abnormal GAregulated initiation and endo-reduplication Trichomes develop in four steps: initiation, endo-reduplication, branching and expansion [36][37][38][39][40][41][42]. To assess the developmental deficiencies of trichome in dxr, we examined the expression of the regulators involved in different steps of trichome development.…”
Section: Dxr Transcript Level Affects the Transcription Of Many Genesmentioning
confidence: 99%